Kemitraan Program Dakwah Ekstrakurikuler Yayasan Al-Khoiriyah Puger-Jember-Jawa Timur: kemitraan program dakwah Ekstrakurikuler - Pramita Syarif Ali (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2022)
Abstract: This research is motivated by the development of the quality of the foundation through the cooperation and partnership of a foundation da'wah program. Foundations that oversee formal educational institutions have different strategies and decision-making with targeted goals and special considerations in determining the program decisions to be realized. This study focuses on the concept, pattern and implementation of the agreed da'wah program. The approach used in this research is a descriptive qualitative approach. Several methods were used to collect data, including observation, documentation, and interviews. Data analysis includes data reduction, data presentation, and data validation. The results show that: first, the concept of the da'wah program, namely the leadership of the foundation, designs a program idea that will be discussed with the parties within the foundation. Second, the pattern of the da'wah program, namely the program design, will be followed up by seeing how much impact will be obtained later in the form of an initial design. Third, implementation, namely joint partnerships with resource persons whose implementation was carried out significantly as well as partnering with extracurricular programs in the form of local taklim majlis in the area around the school environment. Then do a partnership with the scholars who are resource persons in the Mauidzatul Hasanah program in the form of religious lectures. Keywords: Foundation, Partnership, Da'wah Program, Extracurricular